Cloning and molecular characterization of thiol-specific antioxidant gene of Leishmania tropica Turkey isolate - Ozavci, Hamza; Kaplan, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2019)
Background/aim: Thiol-specific antioxidant (TSA) protein is one of the most promising molecules among candidates for vaccine against cutaneous leishmaniasis. It was found to be significantly protective against different Leishmania species. In this study, cloning and molecular characterization of thiol-specific antioxidant gene of L. tropica Turkey isolate (LtTSA) were aimed. Materials and methods: LtTSA was amplified by PCR using the specific primers of TSA gene and cloned into the pcDNA3.1 vector. The cloning was confirmed by PCR screening, restriction enzyme reactions, and DNA sequence analysis. Finally, three-dimensional structure and antigenic properties of the protein encoded by the LtTSA were determined. Results: Six hundred base pair bands belonging to LtTSA were shown with electrophoresis. It was found that LtTSA and its encoded protein have high similarity with different Leishmania species. DISA protein consisting of 199 amino acids was found to have 7 different antigenic regions. Conclusion: LtTSA and its encoded TSA protein were found to be highly immunogenic and similar to TSA proteins previously tested as a vaccine candidate.
Keywords: Cutaneous leishmaniasis; Thiol-specific antioxidant; cloning; DNA vaccine